2017
DOI: 10.1080/02770903.2017.1391282
|View full text |Cite
|
Sign up to set email alerts
|

Subjective responses to sprint interval exercise in adults with and without Exercise-induced bronchoconstriction

Abstract: Perceived breathlessness may impact affect during the early stages of exercise among those with EIBC. Post-exercise enjoyment appears to be similar between SPRINT and MOD. Future research is needed to better understand the relationship between ventilation patterns, exercise intensity, and enjoyment of exercise among those with EIBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…A total of 31 publications involving 1,060 participants met the inclusion criteria. We contacted the authors of nineteen studies and relevant data were received directly from 17 authors (Astorino & Thum, 2016;Bartlett et al, 2011;Farias-Junior et al, 2019;Good & Dogra, 2017;Greene, Greenlee, & Petruzzello, 2018;Hoekstra, Bishop, & Leicht, 2017;Monroe et al, 2016;Niven et al, 2018;O'Neill & Dogra, 2017;Olney et al, 2018;Poon, Sheridan, Chung, & Wong, 2018;Rizk et al, 2015;Songsorn et al, 2019;Stork, Gibala, & Martin Ginis, 2018;Thum, Parsons, Whittle, & Astorino, 2017;Tsukamoto et al, 2016;Wilke et al, 2019), and we extracted data from three figures in the original papers (Foster et al, 2015;Siemens, 2013). Data reported in Decker and Ekkekakis (2017) were extracted from the published thesis (Decker, 2009), but additional data from the thesis were unavailable and these outputs are reported as one study.…”
Section: Inclusion Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 31 publications involving 1,060 participants met the inclusion criteria. We contacted the authors of nineteen studies and relevant data were received directly from 17 authors (Astorino & Thum, 2016;Bartlett et al, 2011;Farias-Junior et al, 2019;Good & Dogra, 2017;Greene, Greenlee, & Petruzzello, 2018;Hoekstra, Bishop, & Leicht, 2017;Monroe et al, 2016;Niven et al, 2018;O'Neill & Dogra, 2017;Olney et al, 2018;Poon, Sheridan, Chung, & Wong, 2018;Rizk et al, 2015;Songsorn et al, 2019;Stork, Gibala, & Martin Ginis, 2018;Thum, Parsons, Whittle, & Astorino, 2017;Tsukamoto et al, 2016;Wilke et al, 2019), and we extracted data from three figures in the original papers (Foster et al, 2015;Siemens, 2013). Data reported in Decker and Ekkekakis (2017) were extracted from the published thesis (Decker, 2009), but additional data from the thesis were unavailable and these outputs are reported as one study.…”
Section: Inclusion Of Studiesmentioning
confidence: 99%
“…Study characteristics are summarised in Table 2. Nineteen of the 33 included studies used a cross-over design comparing HIIE with MICE (Astorino & Thum, 2016;Bartlett et al, 2011;Decker & Ekkekakis, 2017;Farias-Junior et al, 2019;Gomes et al, 2018;Good & Dogra, 2017;Greene et al, 2018;Hoekstra et al, 2017;Little et al, 2014;Monroe et al, 2016;O'Neill & Dogra, 2017;Olney et al, 2018;Ong, Wallman, Fournier, Newnham, & Guelfi, 2016;Saanijoki, Tuominen, et al, 2018;Songsorn et al, 2019a, b;Stork et al, 2018;Thum et al, 2017;Tsukamoto et al, 2016).…”
Section: Descriptive Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, some, but not all studies [69] have reported more modest decreases in FEV 1 in response to HIIT (90% W max for 1 minute followed by 10% of W max for 1 minute, repeated 10 times; FEV 1 -7% ± 8%) when compared with moderate intensity continuous training programs (completed at 65% W max ; FEV 1 -15% ± 12%) [40,70]. Similarly, the effects of HIIT compared with continuous training approaches on dyspnoea and rating of perceived exertion experienced during training are also disparate [71,72]. Studies which included a warm-up period, rather than commencing with work intervals by cycling 'as fast as possible' without any resistance on the pedals appeared to induce less bronchoconstriction [70].…”
Section: Asthmamentioning
confidence: 99%